Mutant Ahi1 Affects Retinal Axon Projection in Zebrafish via Toxic Gain of Function - Zhu, Louyin; Chen, Laiqiang; Yan, Lingya; Perkins, Brian D.; Li, Shihua; Li, Baoming; Xu, Hong A.; Li, Xiao-Jiang (Frontiers in Cellular Neuroscience, 2019)
Joubert syndrome (JBTS) is an inherited autosomal recessive disorder associated with cerebellum and brainstem malformation and can be caused by mutations in the Abelson helper integration site-1 (AHI1) gene. Although AHI1 mutations in humans cause abnormal cerebellar development and impaired axonal decussation in JBTS, these phenotypes are not robust or are absent in various mouse models with Ahi1 mutations. AHI1 contains an N-terminal coiled-coil domain, multiple WD40 repeats, and a C-terminal SH3 domain, suggesting that AHI1 functions as a signaling or scaffolding protein. Since most AHI1 mutations in humans can result in truncated AHI1 proteins lacking WD40 repeats and the SH3 domain, it remains unclear whether mutant AHI1 elicits toxicity via a gain-of-function mechanism by the truncated AHI1. Because Ahi1 in zebrafish and humans share a similar N-terminal region with a coiled-coil domain that is absent in mouse Ahi1, we used zebrafish as a model to investigate whether Ahi1 mutations could affect axonal decussation. Using in situ hybridization, we found that ahi1 is highly expressed in zebrafish ocular tissues, especially in retina, allowing us to examine its effect on retinal ganglion cell (RGC) projection and eye morphology. We injected a morpholino to zebrafish embryos, which can generate mutant Ahi1 lacking the intact WD40 repeats, and found RGC axon misprojection and ocular dysplasia in 4 dpf (days post-fertilization) larvae after the injection. However, ahi1 null zebrafish showed normal RGC axon projection and ocular morphology. We then used CRISPR/Cas9 to generate truncated ahi1 and also found similar defects in the RGC axon projection as seen in those injected with ahi1 morpholino. Thus, the aberrant retinal axon projection in zebrafish is caused by the presence of mutant ahi1 rather than the loss of ahi1, suggesting that mutant Ahi1 may affect axonal decussation via toxic gain of function.